A hybrid deep learning approach for intrusion detection in iot networks - EMEÇ, MURAT (My University, 2022)
Internet of Things (IoT) devices have flocked the whole world through the Internet. With increasing mission critical IoT data traffic, attacks on IoT networks have also increased. Many newly crafted attacks on IoT communication require equally intelligent intrusion detection methods to form the first step of countering the attacks. Our work contributes to intrusion detection in IoT networks, by putting state-of-the-art Deep learning methods into service. A BLSTM-GRU Hybrid (BGH) model has been designed to detect eight known IoT network attacks, based on two well-accepted CIC-IDS-2018 and BoT-IoT IoT network traffic datasets. The results of our BGH model in IoT network traffic intrusion detection have been auspicious. The accuracies of prediction on the two datasets are 98.78% and 99.99%. The f1-scores are 98.64% and 99.99%, respectively. The comparison of our results with similar previous studies showed that our BGH model has the best performance ratio (time/accuracy, time/f1-score), where time is the training time of the model. The performance of our proposed model is proof that hybrid Deep Learning methods can prove to be an innovative perspective on Intrusion Detection in IoT networks.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Engineering and Technology; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE; Engineering, Computing & Technology (ENG); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; General Engineering; Artificial Intelligence; General Computer Science; Engineering (miscellaneous); Electrical and Electronic Engineering; Computer Science (miscellaneous); Computer Vision and Pattern Recognition; Computer Science Applications; Physical Sciences; hybrid intelligent systems; Internet of Things; intrusion detection; learning systems; prediction methods